2006
DOI: 10.1177/0164027505281560
|View full text |Cite
|
Sign up to set email alerts
|

Late-Life Emergence of Early-Life Trauma

Abstract: This study aimed to provide preliminary evidence for, and explore potential antecedents and correlates of, a phenomenon observed in aging combat veterans termed late-onset stress symptomatology (LOSS). LOSS is a hypothesized phenomenon among older veterans who (a) experienced highly stressful combat events in early adulthood; (b) functioned successfully throughout their lives, with no chronic stress-related disorders; but (c) begin to register increased combat-related thoughts, feelings, reminiscences, memorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 42 publications
(43 reference statements)
1
32
0
Order By: Relevance
“…For example, it would be useful to know the level of combat-PTSD prior to the cancer diagnosis, as it is possible that our post-cancer measurement of combat-PTSD symptoms was contaminated by the cancer experience. The experience of cancer could have triggered a reemergence of combat stress-related symptoms for some (Davison et al, 2006). In this instance we were only able to acquire data 6-and 12-months postdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it would be useful to know the level of combat-PTSD prior to the cancer diagnosis, as it is possible that our post-cancer measurement of combat-PTSD symptoms was contaminated by the cancer experience. The experience of cancer could have triggered a reemergence of combat stress-related symptoms for some (Davison et al, 2006). In this instance we were only able to acquire data 6-and 12-months postdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A. Anderson et al symptomology (LOSS; Averill & Beck, 2000;Davison et al, 2006;Yehuda et al, 2009). Researchers have also found that individuals who have experienced early-life trauma may become more vulnerable to maladies of health and compromised well-being and functioning as they age (e.g., Davison et al, 2006;Graziano, 2003).…”
mentioning
confidence: 99%
“…Anderson et al symptomology (LOSS; Averill & Beck, 2000;Davison et al, 2006;Yehuda et al, 2009). Researchers have also found that individuals who have experienced early-life trauma may become more vulnerable to maladies of health and compromised well-being and functioning as they age (e.g., Davison et al, 2006;Graziano, 2003). Providing care to older adults who have experienced early-life trauma can be challenging, as past memories of these difficult experiences impact their reactions to caregiving activities (e.g., bathing, dressing) and environmental factors (e.g., lighting, smells, uniforms; David & Pelly, 2003).…”
mentioning
confidence: 99%
“…In Sierra Leone, it is important to note that a number of programs have evolved to attend to the consequences of rape and other forms of gender-based violence, however very little attention has been given to addressing the mental health consequences of perpetrating atrocities. Certainly research from other wars has indicated that such experiences have profound developmental consequences and pose persistent risks for mental health problems (Davison et al, 2006;Grossman, 1996;King & King, 1999).Without more targeted attention to support these young people to make the best of the opportunities available to them in development efforts, the risks facing this particularly vulnerable cohort are likely to become more intractable. Such lost opportunity will have personal consequences for the youth in question, a compelling enough reason to act on human rights grounds alone.…”
mentioning
confidence: 99%